ANALISIS PENGEMBANGAN USAHA COFFEE SHOP DENGAN PENDEKATAN PEST PASCA PANDEMI COVID-19 DI KOTA DENPASAR - I Wayan Sunia; I Gusti Ngurah Putra Suryanata; I Made Suidarma; I Dewa Nyoman Marsudiana; Made Arya Segara Wilis; I Nyoman Taun (STIE BIITM, 2022)
ABSTRACTAnalysis of Coffee Shop Business Development with the Post-Covid-19 PEST Approach in Denpasar City. This study intends to understand the effect of the analysis of coffee shop business development with the PEST approach after the Covid-19 pandemic in Denpasar city, with a sample of 48 respondents and using saturated sampling techniques in sampling. The data collection technique used a questionnaire using a Likert scale. The type of data in this study uses quantitative data the data analysis method used is validity test analysis, reliability test, classical assumption test, multiple regression analysis, coefficient of determination, partial significance test (t test), and simultaneous test (t test). The result of study prove that partially, politics has a positive and significant influence in increasing the development of the Coffee Shop business in the city of Denpasar, this can be seen from the results of the t-test, namely the t coefficient is 3,465. The economy has a positive and significant influence in increasing the coffee shop business development in the city of Denpasar, this can be seen from the results of the t-test, namely the t coefficient is 3,588. Social has a positive and significant influence in increasing the coffee shop business development in the city of Denpasar, this can be seen from the results of the t test, namely the t coefficient is 2,958. Technology has a positive and significant influence in increasing the coffee shop business development in the city of Denpasar, this can be seen from the results of the t-test, namely the t coefficient is 2.436. Simultaneously Politics, Economy, Social and technology have a positive and significant influence on the Coffee Shop Business Development in Denpasar City by 55.10%, while the remaining 45.90% is influenced by other factors that are not discussed in this study.Keywords: Political, Economic, Social, Technological and Business Development ABSTRAK Penelitian ini bermaksud untuk memahami Pengaruh Analisis Pengembangan Usaha Coffee Shop dengan Pendekatan PEST Pasca Pandemi Covid-19 di Kota Denpasar, dengan sampel 48 responden dan menggunakan teknik sampel jenuh dalam pengambilan sampel. Teknik pengumpulan data menggunakan kuisioner dengan menggunakan skalalikert. Jenis data yang dalam penelitian ini memakai data kuantitatif. Metode analisis data yang digunakan ialah analisis uji validitas, uji reliabilitas, uji asumsi klasik, analisis regresi berganda, Koefisien determinasi, uji signifikan parsial (uji t), dan uji simultan (uji f). Hasil penelitian membuktikan bahwa secara parsial politik memiliki pengaruh positif dan signifikan dalam meningkatkan pengembangan usaha Coffee Shop di kota Denpasar, ini dapat dilihat dari hasil uji t-test yaitu koefisien t diperoleh sebesar 3.465. Ekonomi memiliki pengaruh positif dan signifikan dalam meningkatkan pengembangan usaha Coffee Shop di kota Denpasar, ini dapat dilihat dari hasil uji t-test yaitu koefisien t diperoleh sebesar 3.588. Sosial memiliki pengaruh positif dan signifikan dalam meningkatkan pengembangan usaha Coffee Shop di kota Denpasar, ini dapat dilihat dari hasil uji t-test yaitu koefisien t diperoleh sebesar 2.958. Teknologi memiliki pengaruh positif dan signifikan dalam meningkatkan pengembangan usaha Coffee Shop di kota Denpasar, ini dapat dilihat dari hasil uji t-test yaitu koefisien t diperoleh sebesar 2.436. Secara simultan Politik, Ekonomi, Sosial dan teknologi memiliki pengaruh positif dan signifikan terhadap Pengembangan Usaha Coffee Shop di Kota Denpasar sebesar 55,10%, sedangkan sisanya sebesar 45,90% dipengaruhi oleh faktor lain yang tidak dibahas pada penelitian ini.Kata kunci : Politik, Ekonomi, Sosial, Teknologi, dan Pengembangan Usaha